How spatial planning can enable pathways to the implementation of sustainable urban drainage systems in the city bowl, Cape Town - Harvey, Catherine (School of Architecture, Planning and Geomatics, 2018)
The dramatic global trend of population growth has led to a rapid urbanisation, resulting in unprecedented land cover change. The incarnation of accompanying developed has typified impermeable surfaces. These surfaces have disconnected the stormwater component of the natural hydrological cycle, disregarding it as a nuisance and designing it to be rapidly removed from urban areas. Utilising Sustainable Urban Drainage Systems (SUDS) offers opportunities in urban areas to recycle the water and challenge the perception that stormwater is a nuisance and of no value. The current context of drought experienced by Cape Town has highlighted the need for less reliance on surface water resources; implementing SUDS could be a way of reconnecting the hydrological urban water cycle. It could also help to repair the human disconnect from nature that is prevalent in urban areas. The research question explored the role of spatial planning in enabling the implementation of SUDS in the City Bowl, Cape Town. While conceptual and technical frameworks have been developed for SUDS in South Africa, at present there is no spatial guide as to how these interventions could be realised in a specific context and area. This research utilise s the tools of spatial planning to re-imagine the City Bowl in relation to water. The case study methods used, enabling a detailed understanding of the site. This was complemented by interviews with various planning professionals in order to understand the current role spatial planning plays in terms of implementing SUDS. The research suggest is that whilst SUDS has many constraints, the opportunities that they provide for improving water quality and quantity, and surrounding amenities, suggests that this is one which has to be embraced if the City Bowl is going to respond innovatively and sustainably to the drought. It also highlights the need to improve coordination across different spheres and departments of governance, and emphasises the need to value local community knowledge. A prevalent silo approach to complex problems is no longer acceptable. The implications of the research are that implementing SUDS in the City Bowl requires planners to embrace a water literacy approach to spatial plans, and in doing so, return the focus to water